Palliative Care: knowledge and feelings of the nurse working in internal medicine and infectious and contagious diseases units of a general hospital: a qualitative study - Marina Borges Teixeira; Loraine Martins Diamente (Universidade Federal Fluminense, Escola de Enfermagem Aurora de Afonso Costa, 2008)
This study originated from the author's concern about providing care to patients at life's end, as she observed that this care was not approached in a holistic manner. Regardless of the patients' prognoses, the nurse is the health care professional who spends most of the day next to the patients and thus needs to be prepared to care for their bio-psycho-social-spiritual needs at any time of their lives. In order to meet the needs of terminally ill patients, palliative care emerged, aiming at comforting and relieving the pain of those who experience it. After assessing the knowledge on palliative care held by nurses working in internal medicine and infectious and contagious diseases units of a general hospital and providing assistance to terminally ill patients, the author verified that the care offered was predominantly based on a biomedical model. Therefore, this justifies the need to approach the issues of death and dying with more emphasis in nursing undergraduate education.